Postural responses to cute animal pictures: The effect of image size - Nonoka Nakamura; Akihiko Gobara; Hiroshi Nittono (Acta Psychologica, 2025)
Affective stimuli are known to induce not only physiological but also postural changes. However, previous studies have reported inconsistent results regarding forward leaning responses to pleasant stimuli, possibly due to confounding variables. This study addressed this issue using cute animal pictures, positive stimuli associated with approach motivation. Forty-one university students were asked to stand on a force plate while viewing animal pictures presented in large or small size, with instructions to imagine interacting with the animals. The results showed that pleasant pictures were rated cuter than neutral or unpleasant pictures. Participants' center of pressure (COP) shifted forward for pleasant pictures and backward for unpleasant pictures. Larger pictures produced more posterior shift in the COP than small pictures for unpleasant and neutral images, while pleasant pictures showed no difference by size. This study demonstrates that forward leaning responses to positive visual stimuli occur when the stimuli have motivational values and that picture valence and size interactively influence postural changes.